Model Kewirausahaan Sosial Berbasis Ekonomi Kreatif dalam Mendukung Sektor Pariwisata di Kota Tasikmalaya - Pandu Adi Cakranegara; Dedi Rianto Rahadi; Sujana Donandi Sinuraya (Jurnal Manajemen dan Kewirausahaan, 2020)
Covid19 contributed to various fields of life including one of the handicraft industries     in Tasimalaya. The craftsmen in Tasikmalaya asked for difficulties in marketing their products because their demand dropped during the pandemic. This research seeks to develop which social entrepreneurship model is suitable for artisans during the Pandemic. The hope is that by applying this social entrepreneurship model, crafters can have financial sustainability. The study is conducted using observations and interviews as well as Participatory Rural Assessments. Based on the results of research and literature studies, this study proposes several alternative social entrepreneurship models that can be applied. In addition, this research also found an important role as well as the government in creating competitive advantage for craftsmen. https://doi.org/10.26905/jmdk.v8i2.4318